Case Report: The Carotid Body in COVID-19: Histopathological and Virological Analyses of an Autopsy Case Series - Porzionato, Andrea; Emmi, Aron; Contran, Martina; Stocco, Elena; Riccetti, Silvia; Sinigaglia, Alessandro; Macchi, Veronica; Barzon, Luisa; De Caro, Raffaele (Frontiers in Immunology, 2021)
Various authors have hypothesized carotid body (CB) involvement in Coronavirus Disease 2019 (COVID-19), through direct invasion or indirect effects by systemic stimuli (‘cytokine storm’, angiotensin-converting enzyme [ACE]1/ACE2 imbalance). However, empirical evidence is limited or partial. Here, we present an integrated histopathological and virological analysis of CBs sampled at autopsy from four subjects (2 males and 2 females; age: >70 years old) who died of COVID-19. Histopathological, immunohistochemical and molecular investigation techniques were employed to characterize Severe Acute Respiratory Syndrome – Coronavirus 2 (SARS-CoV2) viral invasion and inflammatory reaction. SARS-CoV2 RNA was detected in the CBs of three cases through Real-Time Reverse Transcription Polymerase Chain Reaction (RT-PCR). In these cases, positive immunostaining for Nucleocapsid and Spike protein were also demonstrated, mainly at the level of large roundish cells consistent with type I cells, confirming direct CB invasion. In these cases, T lymphocytes showed focal aggregations in the CBs, suggestive of local inflammatory reaction. Blood congestion and microthrombosis were also found in one of the positive cases. Intriguingly, microthrombosis, blood congestion and microhaemorrages were also bilaterally detected in the CBs of the negative case, supporting the possibility of COVID-19 effects on the CB even in the absence of its direct invasion. SARS-CoV-2 direct invasion of the CB is confirmed through both immunohistochemistry and RT-PCR, with likely involvement of different cell types. We also reported histopathological findings which could be ascribed to local and/or systemic actions of SARS-CoV-2 and which could potentially affect chemoreception.